The clinical course of critically ill COVID-19 patients receiving invasive mechanical ventilation with subsequent terminal weaning: Primary data from 11 cases. Issue 16 (23rd April 2021) - Liu, Yulan; Xie, Wenjie; Meng, Yang; Sun, Lifang; Yan, Juanjuan; Dong, Weiguo; Zhou, Chenliang; Yu, Zhui
Abstract : Abstract: The coronavirus disease (COVID-19) outbreak was first reported in December 2019 in Wuhan, China. Specific information about critically ill COVID-19 patients receiving invasive mechanical ventilation (IMV) is rare. To describe the clinical course and complications of critically ill patients with COVID-19 who received IMV and were successfully weaned from it. This retrospective study included patients admitted to 3 intensive care units (ICUs) and 1 sub-ICU of Renmin Hospital of Wuhan University and Wuhan Jin Yin-tan Hospital between December 24, 2019, and March 12, 2020. Eleven patients who had been diagnosed with critically ill COVID-19 according to the World Health Organization interim guidance, received invasive ventilation, and were finally successfully weaned from it, were enrolled in our study. Their presenting symptoms, comorbidity conditions, laboratory values, ICU course, ventilator parameters, treatments, and relative complications were recorded. Of 108 critically ill COVID-19 patients who received invasive ventilation, 11 patients who underwent tracheal extubation or terminal weaning were included. The mean age of the 11 patients was 52.8 years (range, 38–70 years), 8 (72.7%) were male, and 2 were health care workers. The median time from onset of symptoms to dyspnea was 6.6 days (range, 3–13 days), and the median duration of IMV was 15.7 days (range, 6–29 days). All 11 patients presented with acute severe hypoxemic respiratory failure and received IMV, and 1 patient switched to extracorporeal membrane oxygenation assistance. A lung-protective strategy with lower tidal volume ventilation and proper driving pressure is the main strategy of IMV. All patients had extrapulmonary manifestations, including acute kidney injury, hepatic dysfunction, myocardial damage, and/or lymphopenia. Hospital-acquired infections occurred in 7 (63.6%) patients. Critical COVID-19 illness is characterized by acute hypoxemic respiratory failure and subsequent dysfunction of other organs with a high mortality rate. Correct ventilation strategies and other clinical strategies to improve oxygenation based on the skilled trained group and the availability of equipment are the key methods to rescue lives. Abstract : Supplemental Digital Content is available in the text